1984
DOI: 10.1128/aac.25.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ceftazidime in patients with renal insufficiency

Abstract: The pharmacokinetics of ceftazidime were studied in 14 adult volunteers with different degrees of renal function. The elimination of ceftazidime was totally dependent on renal excretion. The clearance of ceftazidime ranged from 7.5 to 145.1 ml/min and correlated with both renal ceftazidime clearance and creatinine clearance (ClcR). It is recommended that 0.5 to 2.0 g of ceftazidime be given in extended dosages, with intervals dependent on the renal function of the patient. Patients with a ClCR of >50 ml/min sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
33
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 9 publications
10
33
0
Order By: Relevance
“…The volume of distribution of the drug was unaffected by the state of renal impairment, and therefore drug clearance was directly proportional to GFR. Similar results have been reported by Ackerman et al (1984), Fillastre et al (1983), Homer et al (1984a, Leroy et al (1984) and by Welage et al (1984).…”
Section: Cejtazidimesupporting
confidence: 93%
“…The volume of distribution of the drug was unaffected by the state of renal impairment, and therefore drug clearance was directly proportional to GFR. Similar results have been reported by Ackerman et al (1984), Fillastre et al (1983), Homer et al (1984a, Leroy et al (1984) and by Welage et al (1984).…”
Section: Cejtazidimesupporting
confidence: 93%
“…There was a marked reduction in Cltot, reflecting slow elimination of the drug due to the poor renal function of our patients, The clearance rate was much lower than in the patients studied by Ljungberg and Nilsson-Ehle (11,12) and Naber et al (10), the decrease being related to the degree of renal impairment, as also noted in a study by H6ffler et al (7). The slow decline in the serum drug concentration resulted in large AUCs values, four times as large as those obtained in studies of younger subjects (3,7,8) but comparable with those obtained for both elderly patients (11,12) and younger patients with impaired renal function (19). The AUC correlated with renal capacity, as also found by Hfffier et al (7).…”
Section: Resultssupporting
confidence: 68%
“…The Vd of ceftazidime in steady state has been reported to average 0.21 l/kg in normal healthy individuals (4). In contrast to other investigators of patients in different age groups (4,7,(10)(11)(12)(13)19), we found a reduced Vd, possibly related not only to the low total body water content in elderly people (i.e. less water available to dissolve a water-soluble substance such as ceftazidime) but also to the dehydration often seen in the very old during acute infection.…”
Section: Resultsmentioning
confidence: 95%
“…Phase 1 studies have established the PK profile of avibactam in healthy volunteers and shown that avibactam is generally well tolerated and does not affect the PK or safety profile of ceftazidime . As avibactam is, like ceftazidime, predominantly excreted unchanged by the kidney, it is possible that impaired renal function affects avibactam clearance and, as a consequence, its plasma exposure . In the present phase 1 study, the primary objective was to characterize the PK of avibactam in adults with normal renal function and those with varying degrees of renal impairment who were administered a single 100‐mg avibactam dose by intravenous (IV) infusion over 30 minutes.…”
mentioning
confidence: 99%